Physical Activity Protects the Pathological Alterations of Alzheimer’s Disease Kidneys via the Activation of PACAP and BMP Signaling Pathways - Perényi, Helga; Szegeczki, Vince; Horváth, Gabriella; Hinnah, Barbara; Tamás, Andrea; Radák, Zsolt; Ábrahám, Dóra; Zákány, Róza; Reglodi, Dora; Juhász, Tamás (Frontiers in Cellular Neuroscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disorder, with typical amyloid (Aβ) aggregations. Elimination of Aβ precursors via the kidney makes the organ a potential factor in the systemic degeneration leading to AD. PACAP exerts neuroprotective effects in AD, and plays a protective role in kidney pathologies. Increased physical activity is preventive in formation of AD but its detailed mechanism and possible connections with PACAP have not been clarified. In kidneys of AD mice, effects of physical activity were investigated by comparing wild type and AD organs. Aβ plaque formation was reduced in AD kidneys after increased training (TAD). Mechanotransduction elevated PACAP receptor expression in TAD mice and normalized PKA-mediated pathways. BMP4/BMPR1 elevation activated Smad1 expression and normalized collagen type IV in TAD animals. In conclusion, our data suggest that elevated physical activity can prevent the AD-induced pathological changes in the kidney via, at least in part, the activation of PACAP-BMP signaling crosstalk.